EFEKTIFITAS KUMUR-KUMUR MENGGUNAKAN REBUSAN CENGKEH UNTUK MENGATASI NYERI AKUT PADA KARIES GIGI DI TPQ ALHIKMAH TEMANGGUNG - Faradilla, Alivia Diah Faradilla Sukma Parapat; Parmilah, Parmilah; kurniawati, Ratna (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: Dental caries, or tooth decay, is a disease that affects the hard tissues of the teeth due to bacterial activity that causes softening of these tissues, resulting in the formation of a hole in the tooth. Acute pain is characterized by a sudden or slow onset with varying degrees of intensity from mild to severe, with an anticipated or predictable end. Objective: To determine the effectiveness of mouth rinses using clove decoction on reducing pain in dental caries at TPQ Alhikmah Temanggung. Method:qualitative descriptive method by applying case studies. The research subjects in this nursing care were clients with dental caries pain at TPQ Alhikmah Temanggung, totaling 2 patients with a three-day treatment period. Result:The results after being given the action of gargling for 3 days, using clove decoction there was a decrease in the level of pain control in dental caries. Conclusion: Giving clove decoction for mouth rinses has proven effective for acute pain due to dental caries.